Terahertz study on the optical properties of bismuth telluride (Bi2Te3) - Lim, Wen Xiang (2014)
In this report, we will investigate the optical properties and carrier dynamics of topological insulators. Terahertz Time-Domain Spectroscopy (THz-TDS) were conducted in the range of 0.4 - 2.8 THz at temperatures as low as 15 - 300 K, on samples such as single-layer graphene and bismuth telluride (Bi2Te3). The study of single-layer graphene provides the groundwork for understanding the Drude model which could be used to model the 2D surface carrier dynamics of Bi2Te3. Topological insulators are materials with conducting surface states and insulating bulk states. Therefore, the use of Drude-Lorentz model is necessary to study the optical properties and carrier dynamics of Bi2Te3. Within our frequency range, the refractive index of a single-layer graphene,